Does Childhood Reading Disability or Its Continuance Into Adulthood Underlie Problems in Adult-Age Psychosocial Well-Being? A Follow-Up Study. (4th July 2019) - Eloranta, Anna-Kaija; Närhi, Vesa; Ahonen, Timo; Aro, Tuija
ABSTRACT: This follow-up study aimed at a better understanding of the associations of reading disability (RD) with adult-age psychosocial well-being. We compared adult-age psychosocial well-being in 48 individuals (20–39 years) with documented childhood RD but without comorbid disabilities to 37 matched controls. The associations of psychosocial well-being with childhood and adult-age reading fluency were studied in the RD group, controlling for IQ, gender and unemployment. Psychosocial well-being was assessed with commonly used self-report questionnaires. No group differences were found in psychosocial well-being. In the RD group, lower adult-age reading fluency was associated with symptoms of depression, lower self-esteem, and social functioning. Severity of childhood RD was not associated with psychosocial well-being. Thus, reading fluency problems continuing into adulthood appear to be related to adult-age psychosocial well-being. A more holistic approach to studying how RD impacts adult-age well-being is needed, including both the individual's developmental history and current functioning in various domains.